Tanggung Jawab Pendidik Perspektif Abdullah Nashih ‘Ulwan - Ristianah, Niken; Ma’sum , Toha; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2021)
Educators are people who have responsibility in the process of internalizing religious values and strive to create individuals who will have a scientific mindset and will have perfect personalities. Educators also play a strategic role in efforts to shape the character of the nation’s generation through the process of developing the desired personality and values. Eduvators also play role in developing intellectualintelligence, emotional intelligence, spiritual intelligence, and other intelligence. Educators are also trying to develop the interest, talents, abilities, and potential of students. In addition, educators in Islamic education are people who have responsibility for the development of students by seeking all the potential and tendencies that exist in students, both covering the cognitive (knowledge), affective (attitude) domains, and the psychomotor domain (skills). According Abdullah Nashih ‘Ulwan there are several responsibilities that must be carried out by educators for children’s education, namely the responsibility for faith eduction, moral education, physical education, intellectual education, psychological education, social education, and sex education.